Impact of COVID-19 pandemic on food availability and affordability: an interrupted time series analysis in Ghana - Yoshito Kawakatsu; Ohene Damptey; John Sitor; Ruth Situma; Jevaise Aballo; Mrunal Shetye; Hirotsugu Aiga (BMC, 2024)
Abstract Background In Africa, approx. 675 million people were at risk of food insecurity. COVID-19 pandemic is likely to have exacerbated this situation, by damaging populations' access to and affordability of foods. This study is aimed at estimating the impacts of the COVID-19 pandemic on availability and prices of essential food commodities at 20 large markets in Ghana. Methods Data on food availability and food retail prices collected through weekly market-level data during the period from July 2017 to September 2020 were used in this study. We performed interrupted time-series analyses and estimated the percentage increases between the observed and predicted food prices by food group and by region to assess the impact of COVID-19 pandemic on food prices. Results As a result, the impact of COVID-19 on food availability was limited. However, the results of interrupted time-series analyses indicate a significant increase in overall mean food prices in Greater Accra, Eastern and Upper East regions. It was also found that mean price of starchy roots, tubers and plantains significantly increased across regions. Discussion The impact of COVID-19 pandemic on food availability and prices was significant but varied by food type and regions in Ghana. Continuous monitoring and responses are critical to maintain food availability and affordability.